MAD for MATH : THE WIZARD SCHOOL - Baruzzi, Agnese (Italy, White Star Kids, Milan, 2017)
Come along with the wizard's apprentice as he guides you through a very special castle. There you'll discover powerful potions, secret passages, mazes, and more. But it seems the apprentice needs a little help remembering his magic formulas. Using a little addition, subtraction, multiplication, division, and other math skills, children 8 to 10 can save the day!
Grade 3-5.
Keywords: Mathematics -- Juvenile works; Juvenile works